Harnessing the association between morphological, biochemical and fibre quality traits in desi cotton (Gossypium arboreum) genotypes - KUMAR, DEEPAK; SANGWAN, OMENDER; JATTAN, MINAKSHI; KUMAR, SANDEEP; SOMVEER; KOLI, GANESH KUMAR; SINGH, VIVEK (The Indian Journal of Agricultural Sciences, 2024)
An experiment was conducted during the rainy (kharif) seasons of 2019 and 2020 at the research farm of Chaudhary Charan Singh Haryana Agriculture University, Hisar, Haryana to study the relationship between morphological, biochemical and fibre quality parameters in 150 desi cotton [Gossypium arboreum (L.)] genotypes in augmented design. Findings of the experiment indicated that the seed cotton yield per plant was significantly and positively correlated with all the traits except days to first flower (-0.226) and plant height (-0.521), while, negatively correlated with biochemical and fibre quality traits. Thus, while improving other traits, seed cotton yield per plant will also increase. Fibre quality traits like fibre length was significant and positively (0.754) correlated with fibre strength but negatively correlated with seed cotton, suggesting quality and quantity can not be improved simultaneously. Hence selection should be done very precisely that as one can not be compromised. Path analysis also revealed that the maximum contribution towards yield was by the number of bolls per plant (0.57), boll weight (0.33), GOT (0.11) and the number of monopods (0.10). Fibre quality parameters did not show any significant contribution directly or indirectly to seed cotton yield. The five traits, viz. number of bolls per plant, number of monopods, ginning outturn (%), seed index (g) and number of seed per boll can contribute to the improvement in cotton. Overall, the significance of this study lies in its potential to yield improvement in desi cotton.